ANALISIS EVALUASI INDIKATOR KINERJA 'PELABUHAN HIJAU' - Andi Ningrat (FROPIL (Forum Profesional Teknik Sipil), 2022)
The concept of sustainable port development is becoming increasingly important to apply due to abnormal conditions of global environmental change. This is because the port has an important role in the economic development of a country. To overcome environmental pollution originating from the construction and operation of ports, the concept of a “green” Port is a solution. Therefore, many researchers have studied the effect of “green” Port performance indicators with various approaches. This analysis focuses on evaluating “green” Port performance indicators based on a literature study. These studies were conducted in several countries, such as: China, Taiwan, Egypt, England, Singapore, and Turkey using a scoring system that combines AHP and fuzzy methods. The results show that all “green” Port performance indicators can be grouped into the following criteria: 1) air pollution management, 2) solid waste pollution management, 3) liquid waste pollution management, 4) air pollution management, 5) marine habitat protection, 6) Port staff management training, and 7) promotion of the “green” Port concept.